Neuroreceptor Activation by Vibration-Assisted Tunneling - Ross D. Hoehn (1836382) (2015)
G protein-coupled receptors (GPCRs) constitute a large family of receptor proteinsthat sense molecular signals on the exterior of a cell and activate signaltransduction pathways within the cell. Modeling how an agonist activates such areceptor is fundamental for an understanding of a wide variety of physiologicalprocesses and it is of tremendous value for pharmacology and drug design. Inelasticelectron tunneling spectroscopy (IETS) has been proposed as a model for themechanism by which olfactory GPCRs are activated by a bound agonist. We apply thishyothesis to GPCRs within the mammalian nervous system using quantum chemicalmodeling. We found that non-endogenous agonists of the serotonin receptor share aparticular IET spectral aspect both amongst each other and with the serotoninmolecule: a peak whose intensity scales with the known agonist potencies. We proposean experiential validation of this model by utilizing lysergic acid dimethylamide(DAM-57), an ergot derivative and its deuterated isotopologues; we also providetheoretical predictions for comparison to experiment. If validated our theory mayprovide new avenues for guided drug design and elevate methods of in silicopotency/activity prediction. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/srep09990